An easy approach to obtain high piezoelectric properties in hard PZT sintered at 950 °C. Issue 1 (1st January 2023) - Cha, Jae-Min; Ha, Su-Jin; Kim, Jung-hwan; Cha, Hyun-Ae; Choi, Jong-Jin; Hahn, Byung-Dong; Cho, Kyung-Hoon; Yoon, Seog-Young; Ahn, Cheol-Woo
Abstract: A hard Pb(Zr, Ti)O3 (PZT), which has a high electromechanical coupling factor, is used in various piezoelectric devices. However, the sintering temperature of this material is high, approximately 1100–1200 °C, restricting the usage of cheap base metal electrodes in fabrication of multi-layer components. This study shows an easy approach for a hard PZT not only to be sintered at ≤950 °C but also to have excellent piezoelectric properties. For the readers interested in the low-temperature sintering study of a PZT ceramic, it is described how the PZT compositions and additives are selected and how the experiments can be simplified in this manuscript. Consequently, 0.8 Pb(Zr0.475 Ti0.525 )O3 –0.2 Pb[(Mg0.5 Ni0.5 )1/3 Nb2/3 ]O3 + 0.5 wt% MnO2 + 0.1 wt% Li2 CO3 + 0.2 wt% Fe2 O3 (sintered at 950 °C) shows a high k p of 0.62, an excellent mechanical quality factor ( Q m ) of 1, 976, and a piezoelectric constant ( d 33 ) of 350 pC/N.